Global climate impacts of the Atlantic multidecadal variability: a model-based approach - Nicoli', Dario (Università Ca' Foscari Venezia, 2019)
The Atlantic Multidecadal Variability (AMV) is a low-frequency mode of variability, characterized by a coherent pattern of oscillatory variations in North Atlantic Sea Surface Temperature. It is a natural internal mode which influences the whole climate system, such as Sahel rainfall, U.S. droughts and Atlantic hurricanes frequency. The challenging task is to identify and quantify the impacts due to the AMV and, in this context, climate models plays a crucial role since the observed historical record is too short for a statistical evaluation based on the instrumental data. In this study, the experimental protocol outlined in the Decadal Climate Predictions Project (DCPP – Component C1) is followed, using CMCC-CM2-SR climate model. This work is aimed to assess (1) the global climate impact of the AMV, (2) the atmospheric teleconnection between the Atlantic and the Pacific basins and (3) the influence of the AMV on the North Atlantic Jet.